The Important Roles of Steroid Sulfatase and Sulfotransferases in Gynecological Diseases - Rižner, Tea Lanišnik (Frontiers in Pharmacology, 2016)
Gynecological diseases such as endometriosis, adenomyosis and uterine fibroids, and gynecological cancers including endometrial cancer and ovarian cancer, affect a large proportion of women. These diseases are estrogen dependent, and their progression often depends on local estrogen formation. In peripheral tissues, estrogens can be formed from the inactive precursors dehydroepiandrosterone sulfate and estrone sulfate. Sulfatase and sulfotransferases have pivotal roles in these processes, where sulfatase hydrolyzes estrone sulfate to estrone, and dehydroepiandrosterone sulfate to dehydroepiandrosterone, and sulfotransferases catalyze the reverse reactions. Further activation of estrone to the most potent estrogen, estradiol, is catalyzed by 17-ketosteroid reductases, while estradiol can be formed from dehydroepiandrosterone by the sequential actions of 3-hydroxysteroid dehydrogenase-4-isomerase, aromatase, and 17-ketosteroid reductase. This review introduces the sulfatase and sulfotransferase enzymes, in terms of their structures and reaction mechanisms, and the regulation and different transcripts of their genes, together with the importance of their currently known single nucleotide polymorphisms. Data on expression of sulfatase and sulfotransferases in gynecological diseases are also reviewed. There are often unchanged mRNA and protein levels in diseased tissue, with higher sulfatase activities in cancerous endometrium, ovarian cancer cell lines, and adenomyosis. This can be indicative of a disturbed balance between the sulfatase and sulfotransferases enzymes, defining the potential for sulfatase as a drug target for treatment of gynecological diseases. Finally, clinical trials with sulfatase inhibitors are discussed, where two inhibitors have already concluded phase II trials, although so far with no convincing clinical outcomes for patients with endometrial cancer and endometriosis.